2008
DOI: 10.1093/schbul/sbn095
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance and Functional Competence as Predictors of Community Independence in Schizophrenia

Abstract: Measures of functional competence have been introduced to supplement standard cognitive and neuropsychological evaluations in schizophrenia research and practice. Functional competence comprises skills and abilities that are more relevant to daily life and community adjustment. However, it is unclear whether relevance translates into significantly enhanced prediction of real-world outcomes. The aim of this study was to assess the specific contribution of functional competence in predicting a key aspect of real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…We agree to the consensus that schizophrenia is marked by cognitive impairments that do not appear to be secondary to symptoms and point to localized brain dysfunction. The addition of functional competence to standard cognitive test data [25] yields a significant increase in validity only for concurrent and not for longitudinal prediction of community independence. The specific real-world validity of functional competence is modest and this information is largely redundant with standard cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…We agree to the consensus that schizophrenia is marked by cognitive impairments that do not appear to be secondary to symptoms and point to localized brain dysfunction. The addition of functional competence to standard cognitive test data [25] yields a significant increase in validity only for concurrent and not for longitudinal prediction of community independence. The specific real-world validity of functional competence is modest and this information is largely redundant with standard cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…One study 47 assessed the relation between cognition, functional capacity, and real-world functional outcomes. Among 127 patients with schizophrenia or schizoaffective disorder, cognition predicted performance on a composite, real-world functional outcome measure at residence, schooling, and work during a 10-month follow-up period.…”
Section: Relations Between Cognition and Other Variables In Predictinmentioning
confidence: 99%
“…Leifker et al (Liefker et al, 2009) suggested that performance-based measures of everyday functioning are more directly related to everyday functioning than NP test performance, although other studies have found slightly different results (Heinrichs et al, 2010). Severity of symptoms negatively impacts on everyday functioning in the absence of major correlations with either NP test performance or functional capacity (Bowie et al, 2008, 2010).…”
Section: Introductionmentioning
confidence: 99%